Heterogeneous acid-catalysts for biodiesel production from waste cooking oil - Castanheiro, José (2022)
Biodiesel is a mixture of ‘fatty acid methyl esters’ (FAME) or ‘fatty acid ethyl esters’ (FAEE). It is an environmentally friendly fuel and is biodegradable and not toxic. Biodiesel results from the transesterification reaction between a triglyceride mole cule and three alcohol molecules. This reaction yields three FAME molecules and a glycerol molecule. Usually, the transesterification reaction is done using a base (NaOH or KOH) as catalyst. Figure 31.1 exemplifies the transesterification of tri glycerides with an alcohol to biodiesel and glycerol (Avhad and Marchetti, 2015). The raw material for biodiesel production is edible vegetable oils (e.g. sunflower and soybean), nonedible vegetable oils (e.g. Jatropha oil), WCO, and animal fats (Fonseca et al., 2019; Lima and Castanheiro 2018). However, when the raw material presents a high amount of ‘free fatty acids’ (FFA), these carboxylic acids react with the catalyst (NaOH or KOH), yielding soap. Then, in order to overcome this prob lem, an esterification step before the transesterification reaction will be necessary. Equation 31.1 shows the scheme of esterification of fatty acid with an alcohol.